Service learning as an opportunity to strengthen multi-stakeholder cooperation between family, school, and community - Dybowska, Ewa (Multidisciplinary Journal of School Education, 2025)
Research objectives (aims) and problem(s): The aim of this article is to explore service learning methodology in cooperative partnerships between families, schools, and local communities. Accordingly, the following research question was posed: How can the service learning method support and strengthen cooperation between families, schools, and the local community?Research methods: A desk research method was applied to both scholarly articles and project reports that use the service learning methodology.Process of argumentation: Service learning is an educational method based on learning through experience and is applied in various areas of education. It can also be used to support multi-stakeholder cooperation among schools, families, and the community. These methods benefit students, parents, teachers, schools, and institutions operating in the local community.Research findings and their impact on the development of educational sciences: In today’s context of a rapidly changing pace of life and ongoing social, cultural, and economic transformations, schools are continually seeking new forms of learning. Promoting the idea of service learning may be one way to achieve educational outcomes that meet students’ needs, as learners are not only recipients of knowledge but also actively experience and apply it through their own involvement.Conclusions and/or recommendations: Service learning is successfully implemented in many countries at both the secondary school and university levels. It benefits both learners and the local community. Further areas for the application of this method should be explored. Primary education, in particular, still seems to be an underdeveloped area for service learning. The exploration of the essence of service learning has indicated the necessity of continuing research that substantiates this approach as an effective method for cultivating communicative learning within the interactions between family, school, and community.